Towards a perennial biomass sorghum crop: A comparative investigation of biomass yields and overwintering of Sorghum bicolor x S. halepense lines relative to long term S. bicolor trials in northern Italy. (April 2018) - Habyarimana, Ephrem; Lorenzoni, Carlo; Redaelli, Rita; Alfieri, Michela; Amaducci, Stefano; Cox, Stan
Abstract: The purpose of this work was to assess biomass and grain yields, path modelling of yield components, and perenniality in 97 Sorghum bicolor x S. halepense (SB x SH) lines, and compare their biomass production to a series of 38 historic (1987–2015) biomass SB trials. Perenniality was evaluated as rhizome overwintering, while other traits were scored using standard procedures. Contrary to SB, several SB x SH lines developed rhizomes and overwintered, depending mostly upon increased dosage of SH genome in SB background. A few backcross-derived SB x SH lines overwintered, indicating that perenniality can be introgressed in sorghum using backcrossing approach. SB x SH lines were competitive in terms of grain and aboveground dry biomass yields compared to SB. SB x SH selections outperformed or were comparable to the best commercial biomass SB hybrid checks, and ranked among the best selections from the historic trials. Grain yield in SB x SH lines depended mainly on number of culms, whereas biomass yields depended mainly on plant height, dry mass and fiber mass fractions of dry material, and number of culms. We identified superior dual purpose SB x SH genotypes producing 5–11 and 38–45 t ha −1 of grain and aboveground biomass, respectively, most of which displayed satisfactory overwintering rates (56–100%) and high levels of fiber (61–69%) mass fraction. These lines represent high energy sorghums suitable for biofuel and food production. The best SB x SH crosses for developing perennial biomass and grain sorghums were represented by perennial/perennial, annual/perennial/perennial, and annual/perennial combinations. Highlights: Sorghum bicolor x S. halepense lines were assessed for performance and perenniality. These lines (SB x SH) were compared to SB checks and historic (1987–2015) trials. Contrary to SB, several SB x SH lines developed rhizomes and overwintered. SB x SH lines were competitive in terms of grain and biomass yields relative to SB. Superior perennial dual purpose (high energy) SB x SH genotypes were identified.